Enhancement of liver size by stimulation of intact rat liver with exogenous hepatotrophic factors - Parra, Osório Miguel (1995)
In mammals, liver size is related to animal body weight at the 2.5 to 3% proportion, a ratio mediated by the afflux of hepatotrophic factors. Formulas capable of modifying this ratio have been developed in previous studies on the rat, with enhancement of liver size brought about by intraperitoneal (portal) infusion of exogenous factors such as glucose, amino acids, insulin, glucagon, vitamins, electrolytes, and triiodothyronine. However, the efficacy of these formulations was accompanied by increased animal mortality (PARRA et al.19,20 ). The present study, which was carried out with small methodological modifications on a larger number of rats using daily intraperitoneal injections of a solution of exogenous hepatotrophic factors (40 ml/kg) for seven days, confirms the previous findings, with a 114.16 ± 7.90% enhancement of liver size beyond the expected value for the body weight of the animal. However, the problem of animal mortality was not fully resolved.